New species of the genus Charinus (Amblypygi; Charinidae) from Cusco, Peru - de Armas, Luis F. (2023)
A new species of the genus Charinus Simon, 1892 is described from Santa Teresa District (1436 –1511 m of altitude), La Convención, Cusco, Peru, being this the third Charinus species from this region and the fifth one for this South American country. Its general feature and female gonopods greatly resembles Charinus longitarsus Armas & Palomino-Cardenas, 2016, and C. yanatile Palomino-Cardenas & Armas, 2022, from Cusco, too; but it differs from them by having 16 instead of 14 trichobothria in the distitibia of leg IV; on the other hand, in C. longitarsus the leg I has 30 tarsomeres (43 in the new species); whereas C. yanatiles has larger median ocular tubercle and the first tarsomere of leg I is longer than tarsomeres 1+2 joined. Also, the description of the female gonopods of C. longitarsus is emended and a taxonomic key for the identification of the Peruvian species of Charinus is given. Publicación registrada en Zoobank/ZooBank article registered:LSID urn:lsid:zoobank.org:pub:F00CAB9F-4562-466E-93AD-9C07AB977721Acto nomenclatural/nomenclatural act:Charinus castilloae Armas & Palomino-Cárdenas, 2023LSID urn:lsid:zoobank.org:act:4AC454B0-1DCB-46D4-8379-4876E28E684C